Identifying keystone taxa and metabolisms of epilithic biofilms is crucial to the conservation of stone heritage from biodeterioration - Ma, Chenchen; Zhang, Xiaoying; Wu, Fasi; Liu, Xiaobo (Frontiers in Microbiology, 2025)
BackgroundOutdoor stone heritage accounts for a large portion of UNESCO World Heritage Sites and is an essential carrier of the ancient civilization of our society. Unfortunately, they usually suffer from serious biodeterioration by diverse microbial colonizers, especially when the environment is available. As microbial communities evolve with the environment, it is important to link the bio-deteriogens to biodeterioration processes accurately.MethodsWe used an integrative high-throughput sequencing and comparative metabolomic approach to unravel the biodeterioration of the Leizhou Stone Dog monuments.ResultsThe divergence and similarity of the composition of microbial biofilms colonizing the monuments indicated that photoautotrophic bacteria (e.g., Leptolyngbya, Chroococcidiopsis, and Chloroplast) and nitrifying archaea (e.g., the family Nitrososphaeraceae) and/or bacteria (e.g., Massilia and Bacillus) are the keystone taxa governing the biodeterioration processes. Further, the correlation between the keystone taxa and physicochemical properties confirmed the consistency of the observations of the keystone metabolisms involved in the biodeterioration processes.ConclusionOur study highlights the necessity of a case-by-case diagnosis of the keystone taxa and metabolisms before any therapy, advancing the conservation science of cultural heritage.